constant pressure expression of power law non-newtonian fluid/solid mixture - Iwata, Masashi; Shimo, Takayuki; Tanaka, Takanori; Jami, Mohammed Saedi (2016)
Expression is the separation of liquid from a two-phase solid/liquid system by compression due to movement of the retaining wall. Expression of non-Newtonian fluid/solid mixture is often encountered in the fields of polymer and food industries. However, a reliable method for the design of the expression process has not been established. In this study, we conducted expression experiments of non-Newtonian fluid/solid mixture under a constant pressure condition. As a model suspended particle, cellulose or kieselguhr powder was used. The powder was mixed with an aqueous solution of sodium carboxymethyl cellulose or sodium polyacrylate. The mixture was first preconsolidated in the compression-permeability cell that consisted of a cell cylinder and a piston of 6 cm diameter and then expressed under constant pressure. As the expression advanced, the time course of the thickness of the sample was measured by a dial gauge fitted on the cylinder. The basic consolidation equation was derived by combining the fundamental equation for power law non-Newtonian flow in the cake with the equation of continuity, and was solved numerically using the Runge-Kutta method. The progress of the expression is represented by an average consolidation ratio Uc. The agreement between calculated and experimental Uc was satisfactory when the creep deformation of the material was taken into consideration. It was elucidated that the consolidation time required for attaining a certain degree of primary consolidation depends on the (N+1)/N-th power of the total volume of the solid material , where N is the flow behavior index of the squeezed liquid. On the other hand, the creep constants B, the ratio of creep deformation to the total deformation, and , a measure of the rate of creep deformation, both were found to be -independent parameters, supporting the validity of the assumption made in the theoretical derivation.